Focal Spect Lesions and Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Seven of 10 patients with infantile spasms examined by SPECT at Tokushima University School of Medicine, Japan, showed localized cerebral hypoperfusion in the temporal lobes.